2012
DOI: 10.1021/sb3000194
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Large, High G+C Bacterial DNA Fragments in Yeast

Abstract: The ability to assemble large pieces of prokaryotic DNA by yeast recombination has great application in synthetic biology, but cloning large pieces of high G+C prokaryotic DNA in yeast can be challenging. Additional considerations in cloning large pieces of high G+C DNA in yeast may be related to toxic genes, to the size of the DNA, or to the absence of yeast origins of replication within the sequence. As an example of our ability to clone high G+C DNA in yeast, we chose to work with Synechococcus elongatus PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 35 publications
0
61
0
2
Order By: Relevance
“…Previous results cloning large DNA fragments from bacteria with moderately high G + C content (55%) indicated that fragments greater than ca . 150 kb were optimally maintained after addition of a yeast replication origin sequence [17]. With the large bacterial fragments, we demonstrated that adding additional yeast replication origins to the DNA allowed for stable maintenance of a ca .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous results cloning large DNA fragments from bacteria with moderately high G + C content (55%) indicated that fragments greater than ca . 150 kb were optimally maintained after addition of a yeast replication origin sequence [17]. With the large bacterial fragments, we demonstrated that adding additional yeast replication origins to the DNA allowed for stable maintenance of a ca .…”
Section: Resultsmentioning
confidence: 99%
“…Vectors used for cloning and assembly of the ~100 kb fragments and entire P. tricornutum chromosomes were constructed from the template plasmids pBK-RBYV-HIS3URA3 and pBK-RBYV-TRP1URA3 using yeast assembly methods [17,37]. Maps and sequences for both vectors are available in the Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A PCR fragment containing MET15 and 360 bp of the JCVI-syn1.0 vector region was generated using the primers Lin(syn1)_3F_Long and Lin(syn1)_3R, as well as the template JCVI-syn1.0 (MET15) genomic DNA, digested with NotI and SalI, and cloned into pBluescript SK+ digested with NotI and XhoI, to generate the plasmid pYO014. To introduce a spacer sequence to be used as a primer annealing site for later PCR analysis or to separate the MET15 marker from the telomere, which may be affected by transcriptional silencing in the final linearized genome, a short fragment was amplified from the genomic DNA of the cyanobacterium Synechococcus elongatus PCC 7942 (Noskov et al 2012) using the primers Lin(syn1)_2F_Linker and Lin(syn1)_2R_Linker, digested with NotI and SacI, and cloned into pYO014 digested with NotI and SacI to generate the plasmid pYO017. A PCR fragment containing 1000 bp of the JCVI-syn1.0 vector region made with the primers Lin(syn1)_1F and Lin(syn1)_1Ra and the template JCVI-syn1.0 genomic DNA was digested with BamHI and SacI and cloned into pYO017 digested with BamHI and SacI to generate pYO018.…”
Section: Linearization Of Mycoplasma Genomes In Yeastmentioning
confidence: 99%
“…Progress towards this goal has already been made with the development of Mycoplasma mycoides , the first microbe with a chemically synthesized genome [16]. Several years of intensive research were necessary to produce this microbe [46], during which time the advanced techniques of genome transplantation [47] and genome assembly [48] were created, and have since been applied in the engineering of other systems [49]. Furthermore, efforts to model the minimal genome requirement of a microbe have been ongoing for several years, and could lead to the development of highly efficient minimized cell factories for a given purpose [50-52].…”
Section: Engineering a Microbe For Biosynthesismentioning
confidence: 99%